Machine vision augmented reality for pedicle screw insertion during spine surgery. (February 2020) - Nguyen, Nhu Q.; Priola, Stefano M.; Ramjist, Joel M.; Guha, Daipayan; Dobashi, Yuta; Lee, Kenneth; Lu, Michael; Androutsos, Dimitrios; Yang, Victor
Abstract: Implementing pedicle safe zones with augmented reality has the potential to improve operating room workflow during pedicle screw insertion. These safe zones will allow for image guidance when tracked instruments are unavailable. Using the correct screw trajectory as a reference angle for a successful screw insertion, we will determine the angles which lead to medial, lateral, superior and inferior breaches. These breaches serve as the boundaries of the safe zones. Measuring safe zones from the view of the surgical site and comparing to the radiological view will further understand the visual relationship between the radiological scans and the surgical site. Safe zones were measured on a spine phantom and were then replicated on patients. It was found that the largest causes for variance was between each of the camera views and the radiological views. The differences between the left and right cameras were insignificant. Overall, the camera angles appeared to be larger than the radiological angles. The magnification effect found in the surgical site result in an increased level of angle sensitivity for pedicle screw insertion techniques. By designing a virtual road map on top of the surgical site directly using tracked tools, the magnification effect is already taken into consideration during surgery. Future initiatives include the use of an augmented reality headset.